Effect of Mastiguard in the Prevention and Treatment of Subclinical Mastitis in Dairy Cows - P. Suresh Kumar (The Indian Veterinary Journal, 2024)
A study was conducted to assess the efficacy of TANUVAS MASTIGUARD (Teat protect spray with TANUCHEK SCC kit) in dairy cattle during 2018-19 as On farm Trial (OFT) in the Annamangalam village of Perambalur district. Animals in mid lactation were screened with somatic cell count (SCC) test kit and animals had SCC of more than 2.0 lakh and twenty animals were selected for the study. One group of 10 animals was kept as control and the other group of 10 animals were sprayed with teat protect (Mastiguard) for 6 weeks. The observations recorded at weekly intervals. At the end of 6 th week, reduction in SCC of milk was recorded in animals of treatment group (1.5 lakh cells /ml) whereas the SCC remains same in control group (2.7 lakh cells/ml). The net returns from treatment group increased due to increase in milk production and reduction in cost incurred towards treatment. Hence, use of MASTIGUARD was found to be effective in prevention and treatment of subclinical mastitis in dairy cows. It was concluded that, Teat protect spray was effective in treatment of subclinical mastitis and along with TANUCHEK – SCC counter and easier for the veterinary professionals and farmers to detect SCC at field level. By detection of subclinical mastitis, treatment could be initiated at the earliest to prevent further losses by preventing the condition to become a clinical mastitis.